Equivalence of the stability of discrete-time Markov jump linear systems - Mayta Guillermo, Jorge Enrique (2020)
This paper investigates the stability of discrete-time Markov jump linear system of second-order, this type of system is similar to the family of discrete-time Markov jump linear system it is known in classical literature as MJLS. We present some consistent stability definitions for the system, where these types of stability are equivalent as long as the state space Markov chain is finite. In addition, a computational test is presented to analyze the stability of the system. The result is a generalization of classical theory, this implies a contribution to the theory.